Epigenetic Link Between Statin Therapy and Type 2 Diabetes - Ochoa-Rosales, C.; Portilla-Fernandez, E.; Nano, J.; Wilson, R.; Lehne, B.; Mishra, P. P.; Gao, X.; Ghanbari, M.; Rueda-Ochoa, O. L.; Juvinao-Quintero, D.; Loh, M.; W. Zhang; et al. (Diabetes Care, 2020)
OBJECTIVE: To investigate the role of epigenetics in statins' diabetogenic effect comparing DNA methylation (DNAm) between statin users and nonusers in an epigenome-wide association study in blood. RESEARCH DESIGN AND METHODS: Five cohort studies' participants (n = 8,270) were classified as statin users when they were on statin therapy at the time of DNAm assessment with Illumina 450K or EPIC array or noncurrent users otherwise. Associations of DNAm with various outcomes like incident type 2 diabetes, plasma glucose, insulin, and insulin resistance (HOMA of insulin resistance [HOMA-IR]) as well as with gene expression were investigated. RESULTS: Discovery (n = 6,820) and replication (n = 1,450) phases associated five DNAm sites with statin use: cg17901584 (1.12 x 10(-25) [DHCR24]), cg10177197 (3.94 x 10(-08) [DHCR24]), cg06500161 (2.67 x 10(-23) [ABCG1]), cg27243685 (6.01 x 10(-09) [ABCG1]), and cg05119988 (7.26 x 10(-12) [SC4MOL]). Two sites were associated with at least one glycemic trait or type 2 diabetes. Higher cg06500161 methylation was associated with higher fasting glucose, insulin, HOMA-IR, and type 2 diabetes (odds ratio 1.34 [95% CI 1.22, 1.47]). Mediation analyses suggested that ABCG1 methylation partially mediates the effect of statins on high insulin and HOMA-IR. Gene expression analyses showed that statin exposure and ABCG1 methylation were associated with ABCG1 downregulation, suggesting epigenetic regulation of ABCG1 expression. Further, outcomes insulin and HOMA-IR were significantly associated with ABCG1 expression. CONCLUSIONS: This study sheds light on potential mechanisms linking statins with type 2 diabetes risk, providing evidence on DNAm partially mediating statins' effects on insulin traits. Further efforts shall disentangle the molecular mechanisms through which statins may induce DNAm changes, potentially leading to ABCG1 epigenetic regulation.